2023
DOI: 10.1002/cam4.6050
|View full text |Cite
|
Sign up to set email alerts
|

Components and effectiveness of patient navigation programmes to increase participation to breast, cervical and colorectal cancer screening: A systematic review

Abstract: Background Inequalities in cancer incidence and mortality can be partly explained by unequal access to high‐quality health services, including cancer screening. Several interventions have been described to increase access to cancer screening, among them patient navigation (PN), a barrier‐focused intervention. This systematic review aimed to identify the reported components of PN and to assess the effectiveness of PN to promote breast, cervical and colorectal cancer screening. Methods We searched Embase, PubMed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 69 publications
(1,217 reference statements)
0
9
0
Order By: Relevance
“…Numerous studies have demonstrated the effectiveness of patient navigation programmes in improving breast cancer screening rates, reducing disparities and enhancing patient satisfaction 22–26. These programmes have been particularly successful in reaching under-resourced populations and improving access to screening services.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated the effectiveness of patient navigation programmes in improving breast cancer screening rates, reducing disparities and enhancing patient satisfaction 22–26. These programmes have been particularly successful in reaching under-resourced populations and improving access to screening services.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding men: Their median age was 35 [30][31][32][33][34][35][36][37][38][39][40]; 35% had superior education, 14% were unemployed. Fifty-nine percent of those with whom contact had been established were immigrants (N= 1490): 25% came from Subsaharan Africa, 19% from North Africa or the Middle East.…”
Section: Acceptance Rate and Characteristics Of The Studied Populationmentioning
confidence: 99%
“…Despite the potential benefits of patient navigation, its use in women’s health care has not been as widespread as in other patient populations. While there are some studies on patient navigation for women, these have primarily focused on breast and gynecologic cancers [ 15 , 16 ]. A literature review by McKenney et al [ 17 ] highlighted the potential role of patient navigation in women’s health by examining existing programs within various health care settings and identifying current gaps in access to women’s health care.…”
Section: Introductionmentioning
confidence: 99%
“…(Continued on the next page) https://doi.org/10.4069/whn.2024.03 15. Oh J • Patient navigation for women's health…”
mentioning
confidence: 99%